Lifetime Fitness Variation Across the Geographical Range in a Colour Polymorphic Species - Gian Luigi Bucciolini; Chiara Morosinotto; Jon Brommer; Al Vrezec; Peter Ericsson; Lars‐Ove Nilsson; Karel Poprach; Ingar Jostein Øien; Patrik Karell (Ecology and Evolution, 2025)
ABSTRACT The maintenance of variation (i.e., different phenotypes) for heritable traits that are under selection, despite expectations of selection eroding variation and favouring only the fittest phenotype, represents an evolutionary paradox. Here, we studied variation in life‐history traits in five populations of colour polymorphic tawny owls (Strix aluco) across Europe that have been individually studied for 13 years. Tawny owls show heritable plumage colour variation ranging from less pigmented (grey) to more heavily pigmented (brown‐red). The breeding life span (BLS), lifetime egg production (LEP), lifetime reproductive success (LRS) and the number of years skipped between breeding attempts (NYS) varied between the study populations, with LEP and LRS varying across colour morphs in a population‐specific fashion. Thus, grey tawny owl females have higher lifetime fledgling and egg production than brown‐red females in some populations, but vice versa in others. Hence, our findings demonstrate disruptive selection of tawny owl plumage colourations across their European range, which may be one factor maintaining variation in heritable tawny owl colourations.